The Berbers of Morocco a history of resistance - Peyron, Michael 1935- (I. B. Tauris, 2021)
"From the Rif War to the rebellion of 1958, the Berbers (Imazighen) have played a central role in the history of Moroccan resistance to colonialism in the twentieth century. This book provides an in-depth overview of Berber resistance to the French campaigns of 'Pacification', and the subsequent struggle over Berber identity in the independence era. Deeply steeped in Berber history and culture, the author traces the major and minor engagements between French forces and the Berbers in revealing detail, using previously unavailable sources. Relying on a wealth of oral sources and extensive field work, it provides the most complete history to date of one of the most important Berber communities in North Africa."--